Forensic human identification: Generating Y-STR data for the South African population - Reid, Kate Megan (Department of Pathology, 2019)
Salt River Mortuary (SRM), Cape Town, investigates ~3500 cases of unnatural death annually, with an apparent burden of unclaimed bodies. A retrospective review was first undertaken to assess the number of these individuals who remained unidentified. Medicolegal records were examined (2010-2017), and ~9% of cases remained unidentified each year. DNA analysis was performed in 23.5% of cases. At the time of this study, unidentified bodies were in storage for up to two years, pending pauper burial. DNA profiling assists forensic human identification, and the analysis of markers on the Y-chromosome has particular importance in kinship analysis. To evaluate the statistical probability of DNA profiles matching between samples, reference data from the background population is required. Such data for the Y-chromosome is lacking for some populations groups in South Africa (SA). As such this study aimed to generate Y-chromosome data relevant to SA. Second to this, the obtainability of DNA profiles from unidentified decedents at SRM, prior to pauper burial, was investigated. Biological samples were obtained from 653 SA individuals (living: n=480; deceased: n=173) belonging to four major population groups. Following internal validation, samples were processed using the Promega PowerPlex® Y23 System. A cohort-representative subset of DNA profiles were also generated using the forensically validated Next Generation Sequencing (NGS) assay on the MiSeq FGx™ system, to assess concordance. Statistical analysis was performed using Arlequin and STATA packages. Full DNA profiles (i.e. haplotypes) were obtained from 626 samples (African: n=183; Coloured: n=170; Indian/Asian: n=111; White: n=162), with 599 haplotypes being unique to a single individual. Following optimisation, haplotypes were obtained from >99% and 85% of living and deceased individuals, respectively. Haplotypes were generated from numerous individuals stored for over one year, and DNA profile quality was not associated with time between death declaration and sample collection. NGS results confirmed the presence of one micro-variant and resolved allele-calling in five instances where the capillary electrophoresis assay was incorrect. Thus, concordance was observed in 98% of loci reviewed. Overall, haplotypes were successfully obtained for four different SA population groups, including refrigerated decedents, even 887 days after death declaration. This demonstrates that DNA profiling can be successful for decedents and efforts should be made to store DNA profiles for the possibility of familial searching and identification, even after burial. Identification of the multitude of unclaimed bodies at forensic facilities nationwide holds immense value for living family members, and provides closure for the acceptance of death and life thereafter.